Sintering effect on mechanical properties of composites of bovine derived hydroxyapatite (BHA) with titanium - OKTAR, FAİK NÜZHET; GÜNDÜZ, OĞUZHAN; SALMAN, SERDAR (Trans Tech Publications Ltd, 2006)
The aim of this study was to prepare high performance biomaterials suitable for use at load bearing applications with high bioactivity. The hydroxyapatite (HA) was prepared from bovine bones via calcination technique. The bovine derived HA (BHA) was mixed with 5 and 10 wt% metallic titanium (Ti) and the obtained homogenous mixtures were pressed to produce the test samples. The compacts were sintered at temperatures between 1000 and 1300°C. Compression strength, density, and microhardness were measured. SEM and X-ray diffraction studies were also made. The best mechanical properties were obtained between after sintering at 1200-1300°C.
Keywords: Bovine Derived Hydroxyapatite; Mechanical Properties; Sintering; Titanium